The Implementation of Law Number 28 of 2014 in Legal Protection of Musicians' Musical Works in Denpasar Regarding Royalty Collection - Syahnakri, Muhamad; I Made Adi Ananda Permana; I Gede Druvananda Abhiseka; Komang Satria Wibawa (Al-Zayn: Jurnal Ilmu Sosial, Hukum & Politik, 2025)
Indonesia's creative industry, particularly in the music sector, faces significant challenges in optimizing copyright protection for musicians. This study examines the implementation of Law No. 28 of 2014, focusing on the role of Collective Management Organizations in ensuring fair royalty collection in Denpasar. The research employs a juridical-empirical approach, utilizing field observations and interviews with relevant stakeholders, including musicians, business owners, and legal experts. The findings reveal that many musicians in Denpasar struggle to protect their rights due to a lack of understanding of Collective Management Organizations and royalty collection procedures. Business operators, such as coffee shop owners, often fail to meet their legal obligations regarding royalty payments. The study concludes that enhancing the presence and effectiveness of Collective Management Organizations, along with increased outreach and education, is essential for improving copyright protection for musicians and ensuring compliance with the law.